1991
DOI: 10.2307/3431125
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite as the Probable Active Species in the Human Carcinogenicity of Arsenic: Mouse Micronucleus Assays on Na and K Arsenite, Orpiment, and Fowler's Solution

Abstract: Sodium arsenite, potassium arsenite, and Fowler's solution (arsenic trioxide dissolved in potassium bicarbonate) are equally active in the mouse bone marrow micronucleus assay ( 1 10 mg/kg by IPijection). The natural ore orpment (principally AS2S3) was inactive despite blood levels of arsenic of 300 to 900 ng/mL in treated mice at 24 hr. Sodium arsenite was active in three strains ofmice. It is suggested that the human lung cancer observed among arsenic ore smelters and the skin cancer among people exposed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Similar results were reported by MacGregor et al [1990], who ascribed the increase in MN in folate-deficient mice to decreased thymine synthesis and perturbations in nucleotide pools. Sodium arsenite exposure also increased MN frequency in both folate-deficient and folate-sufficient mice, consistent with earlier reports [Tinwell et al, 1991;Tice et al, 1997]. Arsenic's clastogenic effects are well established and may result from DNA damage induced in a variety of ways, including through oxidative stress and interference with DNA repair processes [NRC, 1999].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were reported by MacGregor et al [1990], who ascribed the increase in MN in folate-deficient mice to decreased thymine synthesis and perturbations in nucleotide pools. Sodium arsenite exposure also increased MN frequency in both folate-deficient and folate-sufficient mice, consistent with earlier reports [Tinwell et al, 1991;Tice et al, 1997]. Arsenic's clastogenic effects are well established and may result from DNA damage induced in a variety of ways, including through oxidative stress and interference with DNA repair processes [NRC, 1999].…”
Section: Discussionsupporting
confidence: 86%
“…Arsenite is the most likely environmental carcinogenic species (Tinwell et al, 1991). This laboratory established mouse model to study skin carcinogenesis associated with arsenite exposure and demonstrated that non-toxic (10mg/l) concentration of arsenite in drinking water enhances UV irradiation-induced skin carcinoma in the Skh1 hairless mice (Rossman et al, 2001; Burns et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although epidemiological evidence demonstrates a strong association between arsenic and human cancers [IARC, 1980;NRC, 2000], its mode of action is not known. Arsenite is the most likely environmental carcinogenic species [Tinwell et al, 1991]. Arsenite alone is able to induce chromosome aberrations and aneuploidy [Gurr et al, 1993;reviewed in Rossman, 1998] and also acts as a co-mutagen, probably by inhibiting DNA repair [Li and Rossman, 1989;Lee-Cheng et al, 1994].…”
Section: Introductionmentioning
confidence: 99%